2014
DOI: 10.1111/pan.12538
|View full text |Cite
|
Sign up to set email alerts
|

A new twist in the pediatric difficult airway

Abstract: Difficult intubation of a 2.4 kg ex premature, suspected Pierre Robin Sequence with upper airway obstruction causing respiratory failure. Multiple failed intubation attempts by an experienced pediatric anesthetist using described techniques and adjuncts. A description of a simple new maneuvre using a GlideScope and a stylet. By twisting the stylet into a spiral shape, the endotracheal tube was given improved maneuverability that allowed the intubator to place the endotracheal tube tip to the glottis opening. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Regarding the primary endpoint ("time to intubate") and the "time to ventilate", no significant differences were observed between the conventional Miller laryngoscope, the C-MAC 1 Miller and the Glidescope 1 Core™. However, the Glidescope 1 Core™ enabled a significantly shorter "time to vocal cords" (p < 0.001, 7 [4][5][6][7][8][9][10][11] vs. 12 [7][8][9][10][11][12][13][14][15][16][17][18], Glidescope 1 Core™ vs. Miller laryngoscope; p < 0.01, 7 [4][5][6][7][8][9][10][11] vs. 10 [7-15], Glidescope 1 Core™ vs. C-MAC 1 Miller) and significantly improved the Cormack and Lehane grade (p < 0.001, 1 Core™ vs. C-MAC 1 Miller). Post-hoc comparison revealed no significant differences for the handling and the difficulty of tracheal intubation.…”
Section: Anesthetists With Limited Previous Experiencementioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the primary endpoint ("time to intubate") and the "time to ventilate", no significant differences were observed between the conventional Miller laryngoscope, the C-MAC 1 Miller and the Glidescope 1 Core™. However, the Glidescope 1 Core™ enabled a significantly shorter "time to vocal cords" (p < 0.001, 7 [4][5][6][7][8][9][10][11] vs. 12 [7][8][9][10][11][12][13][14][15][16][17][18], Glidescope 1 Core™ vs. Miller laryngoscope; p < 0.01, 7 [4][5][6][7][8][9][10][11] vs. 10 [7-15], Glidescope 1 Core™ vs. C-MAC 1 Miller) and significantly improved the Cormack and Lehane grade (p < 0.001, 1 Core™ vs. C-MAC 1 Miller). Post-hoc comparison revealed no significant differences for the handling and the difficulty of tracheal intubation.…”
Section: Anesthetists With Limited Previous Experiencementioning
confidence: 99%
“…Due to different blade sizes, these devices can also be used for the management of a difficult airway in infants and newborns [8,9]. In addition, VLs, including the C-MAC 1 [10], the Airtraq 1 [11], the McGrath MAC™ [12] and the Glidescope 1 [13] have been successfully used in pediatric patients with PRS. In a randomized multi-institutional crossover study, Fiadjoe and colleagues even reported comparable first-attempt intubation success of Glidescope 1 Cobalt video laryngoscopy and fiberoptic bronchoscopy when used in a Pierre Robin manikin [14].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, this study has some limitations. First, the effect of twisting the tube into the spiral shape was expected to be more pronounced in difficult intubation cases or for younger infants requiring a small sized blade (blade # 0 or blade # 1), as reported in previous cases 16 . In this study, however, infants without airway anomalies were recruited, and the proportion of infants less than 3 kilograms was small.…”
Section: Discussionmentioning
confidence: 77%
“…Previously, there has been a report of tracheal tube twisting that was successfully used in difficult GlideScope intubation cases 16 . Twisting the tube shaft into a spiral shape seems to provide a sufficient angle that allows the tracheal tube tip to be placed at the center of the laryngeal inlet.…”
mentioning
confidence: 99%
“…One further option is available for difficult intubation in children using the GlideScope ® . It is known that twisting the stylet into a spiral or a cork-screw shape and rotating it while intubation makes it simpler [ 3 ]. Although this maneuver can overcome the difficult angulation, the tracheal tube has to be rotated 180°.…”
Section: Discussionmentioning
confidence: 99%